2015
DOI: 10.3928/01477447-20150402-04
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Dose Recombinant Human Bone Morphogenetic Protein-2 for 3-Level Anterior Cervical Diskectomy and Fusion

Abstract: This study evaluated the safety of 3-level anterior cervical diskectomy and fusion (ACDF) with ultra-low-dose recombinant bone morphogenetic protein-2 (rhBMP-2). Thirty-seven consecutive patients with cervical spondylotic myelopathy who were treated with 3-level ACDF and rhBMP-2 were evaluated. Complications such as airway or cervical swelling or hematoma were not observed. The rate of dysphagia was no different at 1, 2, and 6 months postoperatively compared with reports in the literature without rhBMP-2. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Similarly, Kukreja et al reported lower incidence of postoperative dysphagia with lower rhBMP-2 doses (11). Pourtaheri et al studied the safety and efficacy of a minimum rhBMP-2 dose in three-level ACDF procedures (12). They concluded that the rates of dysphagia in their patients were similar with those of series using no rhBMP-2 (12).…”
Section: Editorialmentioning
confidence: 96%
“…Similarly, Kukreja et al reported lower incidence of postoperative dysphagia with lower rhBMP-2 doses (11). Pourtaheri et al studied the safety and efficacy of a minimum rhBMP-2 dose in three-level ACDF procedures (12). They concluded that the rates of dysphagia in their patients were similar with those of series using no rhBMP-2 (12).…”
Section: Editorialmentioning
confidence: 96%
“…In the final analysis, 29 studies including a total of 1,539,021 cases fulfilled the predefined inclusion criteria and were included ( Figure 1 ). These publications were full-text articles [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. Examination of the references listed for these studies did not yield any further studies for evaluation.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The characteristics of included studies are shown in Table 1 . Among the included studies, there was 1 small sampled RCT without clarified confidence interval and <80% follow-up (level of evidence: 2b) [ 39 ]; 2 prospective nonrandomised, historically controlled trials (level of evidence: 2b) [ 24 , 32 ]; 2 prospective therapeutic cohort studies (level of evidence: 2b) [ 35 , 38 ]; 1 prospective study that collected data prospectively without controls (level of evidence: 4) [ 44 ]; 14 retrospective studies comparing contemporary series of patients (level of evidence: 3b) [ 22 , 23 , 25 , 26 , [28] , [29] , [30] , [31] , 33 , 34 , 37 , 42 , [45] , [46] , [47] ]; 2 retrospective studies using historical series as controls (level of evidence: 4) [ 36 , 41 ] and remaining 7 retrospective studies without controls (level of evidence: 4) [ [19] , [20] , [21] , 27 , 40 , 43 , 48 ]. The primary exposure or intervention was rhBMP-2.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations